2019
DOI: 10.1016/j.heliyon.2019.e02827
|View full text |Cite
|
Sign up to set email alerts
|

Improving the self-regulation in prospective science teachers: the case of the calculus of the period of a simple pendulum

Abstract: This paper addresses the need to perform laboratory activities in secondary education science subjects, and what prospective science teachers feel while they themselves are doing these activities in their initial training. A laboratory activity based on the calculation of the oscillation period of a simple pendulum was done with 12 prospective teachers at the University of Extremadura, who were specializing in Biology/Geology, Physics/Chemistry, and Mathematics. When they had finished the activity they filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 50 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…At a first glance, it is quite interesting to see that the general orientation of the emotions in Education and Engineering group is not as similar as it could be expected. It seems that in pre-service teachers, this activity produced positive emotions in the sense described by Borrachero et al. (2019) towards Science in the students, such as curiosity or intrigue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a first glance, it is quite interesting to see that the general orientation of the emotions in Education and Engineering group is not as similar as it could be expected. It seems that in pre-service teachers, this activity produced positive emotions in the sense described by Borrachero et al. (2019) towards Science in the students, such as curiosity or intrigue.…”
Section: Resultsmentioning
confidence: 99%
“…In case there were differences between the two researchers, the two reached a consensus proposal. In order to categorize the emotions, Bisquerra's definition ( Bisquerra, 2009 ) was taken into account the modification of Borrachero's taxonomy ( Borrachero et al., 2019 ; Borrachero et al., 2014 ). According to these authors, the final taxonomy we used involved three kinds of emotions: positive (or pleasant ones), negative (or disgusting ones) and neutral (those ones that depend on the subject and on the experience, such as surprise).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there still exists a gap in characterizing how these methodologies, different from traditional exclusively orally-based lessons, affect the learning experience [10,31,60]. A few bunch of authors have already pointed out the main role the methodology has on the learning experience, rather than other factors such as the content itself [64] or the academic background [65].…”
Section: Project Based Learning For Science Educationmentioning
confidence: 99%
“…Students can influence their learning through metacognition. It has been demonstrated that there is a loss of motivation and negative emotions when they feel less competent with this scientific content [ 20 ].…”
Section: Introductionmentioning
confidence: 99%